(untitled) (Nigerian Journal of Physiological Sciences, 2020)
A novel pulmonary illness caused by coronavirus 2019 (COVID-19) of unknown origin was first reported in China. This disease has claimed over a million human lives worldwide. This pandemic respiratory disease spread through droplets on surfaces and community spread. Government of different countries adopted a total lockdown to reduce human to human contact and keep families safe from the disease. This compulsory movement restriction reduces physical activity of individuals which could pose cardiovascular risk to physically inactive African population. This brief states the various cultural and one health approaches that could be adopted to increase physical activity within the home setting. Literature search using pubmed, scopus and google scholar and views of one health personnel in the promotion of physical activity at home during the compulsory lockdown were sought for to identify some simple approaches and gaps that need to be researched on. The overview identified culturally related indoor physical activities in Africa such as ampe or tente that could enhance health. It encouraged dog walking, tending backyard farm and catering for indigenous chicken and small ruminants as means of increasing physical activity. Counseling was proffered by nurses to increase health promotion activities such as setting reminders for physical activities and routine house chores. This submission bring to bear indigenous, flexible and simple measures to combat boredom, promote cardiovascular health by increasng physical activity during the compulsory lockdown currently being experienced in Africa, a known cardiovascular risk, physically inactive population